DEVELOPMENT OF A CAREER READINESS ASSESSMENT TOOL BASED ON INTERESTS, POTENTIAL, AND SOFT SKILLS FOR VOCATIONAL HIGH SCHOOL STUDENTS - RIA FEBRIANTI; Wahyu Sakti Gunawan Irianto; Anik Nur Handayani (SOSIOEDUKASI, 2026)
This study aims to develop a career readiness instrument for vocational high school students in the Software Engineering and Computer and Network Engineering programs. The instrument was developed by adapting three main constructs related to career readiness: career interests, individual potential, and soft skills. This study employs an instrument development approach that includes the stages of literature review, formulation of indicators and item statements, expert validation, as well as testing the validity and reliability of the instrument. Interest indicators were adapted from the RIASEC theory proposed by Holland, potential indicators were adapted from Gardner’s Multiple Intelligences concept, while soft skills indicators were adapted from work competency concepts relevant to industry needs. The developed instrument was validated by three experts, consisting of one guidance and counseling expert and two industry practitioners serving as Chief Executive Officer (CEO) and Human Resources (HR) professionals. After undergoing a revision process, the instrument was pilot-tested on 30 vocational high school students in the Software Engineering and Computer and Network Engineering programs. The validity test results showed that most items met the validity criteria, while several items were eliminated because they had correlation values below the specified threshold. The reliability test results showed a Cronbach’s Alpha value of 0.946 for the interest instrument, 0.929 for the potential instrument, and 0.982 for the soft skills instrument, indicating a very high level of internal consistency. The results of this study indicate that the developed instruments are valid and reliable for measuring the career readiness of vocational high school students and can be used as tools in career guidance services in the field of information technology.